COVID-19 THERAPEUTICAL OPTIONS: OVERVIEW ON CURRENTLY ANTIMALARIALS AND ANTIPARASITIC DRUGS USED - Leite Guedes, Idrys Henrique; Dantas dos Santos , Gregório; Freire Viana, Antônio Bonildo; da Silva Araújo, Geldane; Câmara Pinto dos Santos, Tálio; Gonçalves Moreno, Cláudia Jassica; Tavares Donato, Silvia (Health and Society, 2021)
Given the amount of scientific knowledge produced and published daily about the new corovavirus, this study sought to review evidence on some of the drugs used to treat Acute Respiratory Infection Syndrome caused by the COVID-19 virus. Thus, antimalarials and antiparasitics were evaluated regarding chemical and pharmacological aspects, including mechanism of action, toxicity, adverse effects and recommendation for use in the treatment of COVID-19.